Public Service Ads On Disposing of Waste Awareness Method Using Motion Graphic Blender - Nurfatanah Nurfatanah; Agung Triayudi; Deny Hidayatullah (Jurnal Teknik Informatika C.I.T Medicom, 2019)
At present many community service announcements about waste are made using 2D animation with motion graphic methods using some supporting software. In making these advertisements to produce a whole video using some software. This makes the computer's performance slow due to the large number of applications installed and the process of completing the video making takes a long time. Here the author aims to make public service announcements about waste using 3D quality motion graphic blender methods. This animated ad was created using only the blender software at each stage. This ad contains an invitation to the public to properly dispose of waste in place with a combination of motion graphic techniques so that the ad becomes visually appealing. From the results of the rendering test which produced a 2 minute 38 second video which is equal to 3953 frames, the video test found less smoothness of character's hand movements because the keyframe distance was only 14 frames, in motion graphic testing using 100% alpha video results in accordance with the storyboard designed, then in the rendering test using 5 different PC specifications, the conclusion is that the more memory and HDD the PC uses, the less time to complete the rendering process. From 5 times the recommended testing is 8 GB RAM memory and 1 TB HDD with a rendering time of 4 minutes 37 seconds.